Rivers and tides [videorecording (DVD)] : Andy Goldsworthy working with time - Riedelsheimer, Thomas; Goldsworthy, Andy, 1956- (Docurama ; Distributed by New Video, 2004)
Follows Andy Goldsworthy's bohemian free spirit all over the world as he demonstrates and opens up about his creative process. From his long-winding rock walls and icicle sculptures to his interlocking leaf chains and multi-colored pools of flowers. Goldsworthy's painstakingly intricate masterpieces are made entirely of materials found in Mother Nature - who threatens and often succeeds in destroying his art, sometime before it is even finished.